Impaired endothelial barrier function in apolipoprotein M‐deficient mice is dependent on sphingosine‐1‐phosphate receptor 1. Issue 6 (8th March 2016) - Christensen, Pernille M.; Liu, Catherine H.; Swendeman, Steven L.; Obinata, Hideru; Qvortrup, Klaus; Nielsen, Lars B.; Hla, Timothy; Di Lorenzo, Annarita; Christoffersen, Christina
ABSTRACT: Apolipoprotein M (ApoM) transports sphingosine‐1‐phosphate (S1P) in plasma, and ApoM‐deficient mice ( Apom –/– ) have 50% reduced plasma S1P levels. There are 5 known S1P receptors, and S1P induces adherens junction formation between endothelial cells through the S1P1 receptor, which in turn suppresses vascular leak. Increased vascular permeability is a hallmark of inflammation. The purpose of this study was to explore the relationships between vascular leakage in ApoM deficiency and S1P1 function in normal physiology and in inflammation. Vascular permeability in the lungs was assessed by accumulation of dextran molecules (70 kDa) and was increased 40% in Apom –/– mice compared to WT (C57Bl6/j) mice. Reconstitution of plasma ApoM/S1P or treatment with an S1P1 receptor agonist (SEW2871) rapidly reversed the vascular leakage to a level similar to that in WT mice, suggesting that it is caused by decreased plasma levels of S1P and reduced S1P1 stimulation. In a carrageenan‐induced model of inflammation, Apom –/– mice had increased vascular leakage compared with that in WT mice. Adenoviral overexpression of ApoM in Apom –/– mice decreased the vascular leakage compared to adenoviral overexpression of green fluorescent protein. The study suggests that vascular leakage of albumin‐sized particles in ApoM deficiency is S1P‐ and S1P1 ‐dependent and this dependency exacerbates the response to inflammatory stimuli.—Christensen, P. M., Liu, C. H., Swendeman, S. L., Obinata, H., Qvortrup, K., Nielsen, L B., Hla, T., Di Lorenzo, A., Christoffersen, C. Impaired endothelial barrier function in apolipoprotein M‐deficient mice is dependent on sphingosine‐1‐phosphate receptor 1. FASEB J. 30, 2351–2359 (2016). www.fasebj.org